Penerapan Model Pembelajaran Kooperatif Tipe Inside Outside Circle (IOC) terhadap Hasil Belajar IPAS Siswa Kelas IV SD Negeri Mangunharjo - Intan Nirmala Natasya; Leo Charli; Andri Valen (Mataram University, 2026)
Instruction in Natural and Social Sciences (IPAS) for fourth-grade students at SD Negeri Mangunharjo indicates that learning outcomes remain suboptimal; therefore, it is necessary to implement a learning model capable of enhancing student engagement and understanding during the learning process. This study aims to determine the significant completion of the science learning outcomes of fourth-grade students of Mangunharjo State Elementary School after the implementation of the Inside Outside Circle (IOC) Cooperative Learning Model. The research method used is a quasi-experimental pre-test and post-test category. The population in this study were all fourth-grade students of Mangunharjo State Elementary School, totaling 27 students and the research sample was fourth-grade students totaling 27 students, consisting of 17 male students and 10 female students taken by (saturated sampling). The data collection technique used multiple-choice test techniques. The data analysis technique used the z test. Based on the data analysis, the average pre-test value was 50.89 and the average post-test value was 80.30 with a confidence level of α = 0.05, Zcount was 4.97 and Ztable 1.64 because Zcount ≥ Ztable, then, Ha was accepted and Ho was rejected. From the results of the data analysis, it was concluded that the results of the science learning of grade IV students of Mangunharjo State Elementary School after applying the Cooperative Learning Model of the Inside Outside Circle (IOC) type were significantly completed.